Full-Thickness Macular Hole Formation after Internal Limiting Membrane Peeling: Beware the “Omega Sign” - Robert A. Sisk; Okan Toygar (Case Reports in Ophthalmological Medicine)
Purpose. To introduce a clinical sign on spectral domain optical coherence tomography (SDOCT), which may indicate high risk for full-thickness macular hole formation after internal limiting membrane (ILM) peeling. Methods. The preoperative SDOCT images of two patients—one with multilaminar hemorrhage from ruptured retinal artery macroaneurysm and one with serous retinal detachment and severe macular schisis from optic pit maculopathy—who developed full-thickness macular hole (FTMH) after ILM peeling were evaluated retrospectively. Results. On the preoperative SDOCT images of both patients there was a thin bridge of tissue on either side of the foveal center with an outer retinal defect. The photoreceptors were displaced laterally away from the foveal center to create an “omega-” shaped configuration of the remaining tissue. Conclusion. “Omega-” shaped configuration on SDOCT may represent a higher risk of FTMH following ILM peeling. Vitreoretinal surgeons may wish to consider this sign in the process of their surgical decision making.